Injuries and injuries in selected team sports in the opinion of players - Mateusz Berczyński; Marek Napierała; Rafał Gotowski (Journal of Education, Health and Sport, 2017)
The aim of the study was to determine the most common injuries occurring in team games and the problems that result in athletes. The study has been applied method of diagnostic survey and the study involved 150 people. Conclusions: (1) The positive effects of sports is the general improvement in physical function and improving well-being, (2) The negative effects of sports is a pain in the joints, (3) The most common injuries occurred during training, (4) Almost half of the people had been hospitalized and undergoing rehabilitation after traveling injury, (5) The vast majority of respondents do not have a problem back onto the field with a history of injury.